PEDAGOGICAL PROBLEMS IN THE IMPLEMENTATION OF RHODOPE FOLK SONGS AND METHODS FOR OVERCOMING THEM - Borisov, B.I (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2019)
The report presents the Rhodope folklore region as it is the most researched in Bulgaria as most of the songs there have lyrical melodies and lyrics. The most characteristic instrument in this area is the caba bagpipe, which is more suited to the male range and voice, while the female voice cannot always sing the heights because of the large ambition of the Rhodopean song. The most used ornaments in this area are the foreshortening and the group as men, unlike women, sing with less ambition, less ornamentation and elemental rhythm. Each folklore region has its own specific dialect. In Rhodope there is a combination of vowels, which are pronounced widely through the participation of free facial muscles and soft pronunciation of all consonants. The combination of vowels with their varieties makes this dialect soft and sultry, making it vocal. In the Rhodope folklore area, women's speech is in a higher register, thus creating an auditory sense that the sound is directed to the higher resonators, and hence the sound output when singing, approaches the falsetto register. It can be summarized that the pedagogical problems in performing folk songs from the Rhodope folklore area are not small, because it contains such ornaments that require very accurate performance due to the specificity of the song style, the construction of the songs, their large ambition and specific dialect. All this, refined and accompanied by a caba bagpipe, gives an idea of the manner of performing Rhodope folk songs.